Prognostic significance of OX40+ lymphocytes in tumor stroma of surgically resected small-cell lung cancer - Hiroshi Yokouchi; Hiroshi Nishihara; Toshiyuki Harada; Toraji Amano; Takayuki Ohkuri; Shigeo Yamazaki; Hajime Kikuchi; Satoshi Oizumi; Hidetaka Uramoto; Fumihiro Tanaka; Masao Harada; Kenji Akie; et al. (OncoImmunology, 2021)
OX40 (CD134) is a co-stimulatory molecule mostly expressed on activated T lymphocytes. Previous reports have shown that OX40 can be an immuno-oncology target and a clinical biomarker for cancers of various organs. In this study, we collected formalin-fixed paraffin-embedded tumor samples from 124 patients with small-cell lung cancer (SCLC) who had undergone surgery. We analyzed the expression profiles of OX40 and other relevant molecules, such as CD4, CD8, and Foxp3, in tumor stroma and cancer nest using immunohistochemistry and investigated their association with survival. High infiltration of OX40+ lymphocytes (OX40high) in tumor stroma was positively associated with relapse-free survival (RFS) and overall survival (OS) compared with low infiltration of OX40+ lymphocytes (OX40low) (RFS, median, 26.0 months [95% confidence interval (CI), not reached (NR)–NR] vs 13.2 months [9.1–17.2], p = .024; OS, NR [95% CI, NR–NR] vs 29.8 months [21.3–38.2], p = .049). Multivariate analysis revealed that OX40high in tumor stroma was an independent indicator of prolonged RFS. Moreover, RFS of patients with OX40high/CD4high in tumor stroma was significantly longer than that of patients with OX40low/CD4low. The RFS of patients with tumor stroma with OX40high/CD8high was significantly longer than that of patients with tumor stroma with OX40low/CD8high, OX40high/CD8low, or OX40low/CD8low. These findings suggest that OX40+ lymphocytes in tumor stroma play a complementary role in regulating the relapse of early-stage SCLC. Reinforcing immunity by coordinating the recruitment of OX40+ lymphocytes with CD4+ and CD8+ T cells in tumor stroma may constitute a potential immunotherapeutic strategy for patients with SCLC.